EARLY KNEE OSTEOARTHRITIS, DIAGNOSIS CRITERIA AND COMPLEX TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The prevalence of chronic joint diseases, among which osteoarthritis (OA) predominates, continues to grow rapidly throughout the world. Until now, most patients begin to receive adequate treatment only at the stage of organ failure of the joint, when it is no longer possible to significantly slow down the progression of the pathological process. This reduces the effectiveness of the therapy. Early OA is one of the least studied problems. The article discusses the problem of timely detection and comprehensive treatment of early OA